Pelatihan Dasar Microsoft Office Pada SMK Bintang Nusantara - Okta Irawati; Iis Istiqomah; Sutrisno (CV. Multi Kreasi Media, 2023)
Vocational high school (SMK) is one of the vocational education programs that has received attention from the government. Various programs that have been launched by the government aim to produce competent graduates who can meet industry needs. For graduates who wish to develop careers in the office sector, they should master the applications used in offices. The application that needs to be mastered is Microsoft Office. To achieve this, the education and learning process must refer to and be in accordance with the applicable curriculum in accordance with the vision, mission and goals of the school. The alignment of the SMK education curriculum with the world of work has been designed from the start, one of which is through the